From Boardrooms to Bedrooms: Unveiling Workplace Extramarital Affairs - Siti Syahbanu; Muhammad Irfan Syaebani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the impact of power dynamics, gender roles, and organizational structures on extramarital affairs within professional environments. It examines how hierarchical structures and societal conventions influence relationships, frequently to the detriment of women. This research employs interdisciplinary approaches, including Marxist alienation, power-approach theory, and social identity theory, to link workplace infidelity to broader concerns of gender inequity, and corporate accountability. The study seeks to examine the influence of organizational hierarchies on workplace relationships, the significance of cultural notions such as